ХЛОРКАЛИЙГАСТИНГСИТ (K,NA)CA2(FE2+,MG)4FE3+[SI6AL2O22](CL,OH)2: РЕАБИЛИТАЦИЯ И НОВОЕ НАЗВАНИЕ ДАШКЕСАНИТА - Пеков И.В.; Чуканов Н.В.; Нефедова М.Е.; Пущаровский Д.Ю.; Расцветаева Р.К. (My University, 2005)
Dashkesanitc, С1- and K-dominant member of the hastingsitc scries discovered by G. A. Krutov in 1936 and later discredited, was rcvalidated as a mineral species in the amphibolc group by the IMA Commission on New Minerals and Mineral Names from the data of the revision study of the type material from Dashkcsan Co-Fc deposit, the Minor Caucasus, Azerbaijan. It was re-named to chloro-potassichastingsitc in accordance with IMA approved nomenclature of amphibolcs. It is major (>95 vol. %) rock-forming mineral of the amphibolc skam containing also quartz, chlorite, actinolitc, apatite, cpidotc, magnetite, hematite and sulfides. Chloro-potassichas-tingsite occurs as coarse-prismatic crystals up to 1.5 mm. Transculcnt, dark-green, streak greenish-gray, luster vitreous. Brittle, cleavage (110) perfect, fracture stepped. Mohs' hardness ~5, micro-indentation hardness is 770-900 (average 830) kg/mm2. D(meas.) is 3.52, D(calc.) - 3.53 g/cm3. Optically biaxial (-),a 1.728, P 1.749, у 1.751, 2V (mcas) 15°. Dispersion: r> v. Plcochroism is strong: a - light orange-yellow, |3 - dark blue-green, у - dark green-blue. Orientation: Y= b, Z Л с= 11°. Chemical composition of the ncotypc specimen (electron probe, Fc2+/Fc3+ by wet chemical analysis, H2O by Pcnficld method, wt %) is: Na2O 1.07, K.2O3.04, CaO 10.72, MgO2.91, MnO 0.40, FcO 23.48, Fc2O3 7.80, AI2O311.13, SiO2 35.62, TiO2 0.43, F0.14, Cl 4.68, H2O+ 0.54, -O = (C1,F)2 1.12, total 100.84. The empirical formula calculated on the basis of 022(C1,F,OH,O)2 is: (Ко 64Na0 з^о^Са, 9o(Fc3+25Fc^7Mgo.72Mn0o6Alo.o6Tio.o5)H.ii(Si5.89Al2.n)i8O22(Cli.31 OH0.6oFo.o7O0.02)i2- The idealized formula is: (K,Na)Ca2(Fc2+,Mg)4Fc3+[Si6Al2O22](Cl,OH)2 (Z= 2). Crystal structure was studied, R = 0.059. Monoclinic, C2/m. Unit cell dimensions refined from the powder data arc: a = = 9.979(4),fe= 18.035(8), с =5.302(3) A, p = 104.71(4)°, V= 923(/) A3. The strongest lines of X-ray powder pattern (d, A - I[hkl]) arc: 8.53- 100[110]; 3.32- 11[240]; 3.16 - 51[310]; 2.981 - 12[221]; 2.839- 18[330], 2.749 - 23[331, 151], 2.191 - 6[261]. The neotypc specimen is deposited in Fcrsman Mineralogical Museum of the Russian Academy of Sciences, Moscow.
Keywords: 549.643.2